Ultra-deep Large Binocular Camera U-band Imaging of the GOODS-North Field: Depth Versus Resolution *Based on data acquired using the Large Binocular Telescope (LBT). (9th May 2018) - Ashcraft, Teresa A.; Windhorst, Rogier A.; Jansen, Rolf A.; Cohen, Seth H.; Grazian, Andrea; Paris, Diego; Fontana, Adriano; Giallongo, Emanuele; Speziali, Roberto; Testa, Vincenzo; Boutsia, Konstantina; O'Connell, Robert W.; et al.
Abstract: We present a study of the trade-off between depth and resolution using a large number of U -band imaging observations in the GOODS-North field from the Large Binocular Camera (LBC) on the Large Binocular Telescope (LBT). Having acquired over 30 hr of data (315 images with 5–6 minutes exposures), we generated multiple image mosaics, starting with the best atmospheric seeing images (FWHM ≲ 0.″8), which constitute ∼10% of the total data set. For subsequent mosaics, we added in data with larger seeing values until the final, deepest mosaic included all images with FWHM ≲ 1.″8 (∼94% of the total data set). From the mosaics, we made object catalogs to compare the optimal-resolution, yet shallower image to the lower-resolution but deeper image. We show that the number counts for both images are ∼90% complete to U AB  ≲ 26 mag. Fainter than U AB  ∼ 27 mag, the object counts from the optimal-resolution image start to drop-off dramatically (90% between U AB  = 27 and 28 mag), while the deepest image with better surface-brightness sensitivity ( μ U AB  ≲ 32 mag arcsec −2 ) show a more gradual drop (10% between U AB  ≃ 27 and 28 mag). For the brightest galaxies within the GOODS-N field, structure and clumpy features within the galaxies are more prominent in the optimal-resolution image compared to the deeper mosaics. We conclude that for studies of brighter galaxies and features within them, the optimal-resolution image should be used. However, to fully explore and understand the faintest objects, the deeper imaging with lower resolution are also required. Finally, we find—for 220 brighter galaxies with U AB  ≲ 23 mag—only marginal differences in total flux between the optimal-resolution and lower-resolution light-profiles to μ U AB  ≲ 32 mag arcsec −2 . In only 10% of the cases are the total-flux differences larger than 0.5 mag. This helps constrain how much flux can be missed from galaxy outskirts, which is important for studies of the Extragalactic Background Light.